An Integrated Flexible Bioelectrical and Biochemical Monitoring System Based on Spindle-Structured Directional Sweat-Pumping Nanomesh - Wu, Jingzhi; Han, Rongkuan; Ma, Jianfeng; Gong, Jinyi; Guan, Tianxin; Dong, Peiyan; Tang, Hao; Liu, Haidong; Luo, Jinan; Liu, Chang; Li, Yuanfang; Zeng, Degong; et al. (Nano-Micro Letters, 2026)
Wearable epidermal monitoring holds significant importance in health assessment. However, current electronic skins are limited by poor conformability caused by sweat accumulation, discomfort from low breathability and single signal, making long-term, stable, and high-throughput signal recording much challenging. In this study, a spindle-structured directional sweat-pumping nanomesh (SDSN) is developed via electrospinning. By combining multiple asymmetries, including wettability, pore size, and spindle-knots structure, the SDSN establishes synergistic forces that enable unidirectional liquid transport at a rate over 1000 times faster than human sweat production during exercise. To demonstrate the advantages in fluid guidance, a dual-architecture and dual-perspective comparative model framework is constructed. The introduction of Au nanomesh as electrodes allows the Au nanomesh electrode to simultaneously monitor electrochemical and electrophysiological signals, while maintaining excellent skin conformability and motion stability. Additionally, a nanomesh-encapsulated flexible circuit is developed capable of continuous wireless monitoring. This system shows potential for correlation analysis of metabolic energy output and cardiovascular response, making it an ideal tool for health management during intense physical labor and exercise. Highlights: 1 Built via controlled electrospinning, the nanomesh integrates wettability and structural gradients, enabling ultrafast unidirectional liquid transport at speeds up to 4.00 mL min−1 cm−2. 2 An Au nanomesh electrode with high breathability and moisture permeability is designed, offering superior conformability and stretchability for stable on-skin monitoring during motion, along with excellent skin compatibility. 3 The system enables wireless and continuous electrochemical and electrophysiological monitoring, combining sweat biomarkers and electrocardiogram signals for comprehensive health analysis.